The Effects of a Sports Nutrition Education Intervention on Nutritional Status, Sport Nutrition Knowledge, Body Composition, and Performance during Off Season Training in NCAA Division I Baseball Players - Rossi, Fabrcio Eduardo [UNESP]; Landreth, Andrew; Beam, Stacey; Jones, Taylor; Norton, Layne; Cholewa, Jason Michael (Journal Sports Science & Medicine, 2017)
This study investigated the effects of a sport nutrition education intervention (SNEI) on dietary intake, knowledge, body composition, and performance in NCAA Division I baseball players. Resistance trained NCAA Division I baseball players (82.4 +/- 8.2 kg; 1.83 +/- 0.06 m; 13.7 +/- 5 % body fat) participated in the study during 12 weeks of off-season training. Fifteen players volunteered for SNEI while 15 players matched for position served as controls (C) for body composition and performance. The nutrition intervention group (NI) received a 90 min SNEI encompassing energy intake (Kcal), carbohydrate (CHO), protein (PRO), fat, food sources, and hydration. Sport nutrition knowledge questionnaires were administered to NI pre and post. Nutritional status was determined by three-day dietary logs administered to NI pre and post. Body composition and performance (5-10-5 shuttle test, vertical jump, broad jump, 1 RM squat) were measured pre and post for C and NI. Knowledge increased in NI. Pro and fat, but not CHO intake increased in NI. FM decreased pre to post in NI (11.5 +/- 4.8 vs. 10.5 +/- 5.4 kg) but not C (11.3 +/- 4.7 vs. 11.9 +/- 4.5 kg). FFM increased pre to post with no differences between groups. The 5-10-5 shuttle times decreased significantly more in NI (4.58 +/- 0.15 vs. 4.43 +/- 0.13 sec) compared to C (4.56 +/- 0.18 vs. 4.50 +/- 0.16 sec). Jump and squat performance increased pre to post with no differences between groups. Our findings indicate that an off season SNEI is effective at improving sport nutrition knowledge and some, but not all, nutrient intakes and performance measures in Division I baseball players.
Keywords: periodization; collegiate nutrition; lean body mass